Analysis of the main motives of learning foreign languages by future specialists in agricultural and engineering specialties in order to improve them - Polishchuk, A. (Problems of Engineer-Pedagogical Education, 2023)
The article is devoted to the analysis of the main motives for learning foreign languages by future specialists in agricultural engineering. The article considers the importance of a foreign language in training highly qualified specialists in the agricultural sector to expand professional contacts, free exchange of information, diverse and systematic communication, quality education, and, consequently, prestigious highly paid job. The relevance of the article is conditioned by the need to train future specialists in agricultural engineering, whose competitiveness is determined not only by their high qualification in the field of production, but also willingness to solve professional and industrial problems in foreign language communication. It was determined that the use of modern advanced technologies, interactive teaching methods and tools in the educational process plays an important role in the formation of positive motivation of students, and the main mover in learning foreign languages are the motives that motivate future agricultural engineers to learn foreign languages, and also plays an important role in the acquisition of knowledge in specialized disciplines. The analysis of research and publications on the ways and methods of the formation of motives in educational activities of higher education students while studying foreign languages was conducted. The concepts of "motive" and "motivation" and their impact on improving the efficiency of learning foreign language material in foreign language classes are explained. The types of motivations for learning foreign languages are singled out. The main motives that have a significant impact on the active acquisition of knowledge of foreign languages are analyzed. According to the results of a questionnaire that was conducted at the graduate courses of the Higher education institution «Podillia State University», the motives of future specialists in agricultural engineering in the study of foreign languages in the learning process are analyzed. As it turned out, the vast majority of graduate students studied a foreign language in order to find an interesting and promising highly paid job.